Analysis of tunnel support design to withstand spalling induced by blasting. (January 2016) - Mitelman, Amichai; Elmo, Davide
Highlights: We simulated 1D rock spalling and compared to analytical spalling equations. We compared 1D and 2D spalling models to field test results. We proposed different design procedures for heavy spalling and light blast damage. Abstract: This paper presents modeling of rock spalling induced by a dynamic pulse using the finite-discrete element method, for the purpose of tunnel support design to withstand blasting. 1D and 2D model results are compared to analytical spalling equations and field test findings. It was found that only the 2D models are suitable for support design. A distinction between heavy spalling and light rockfall is made based on an estimation of the ratio of the peak stress of the arriving wave to the rock tensile strength. Accordingly, different design approaches are suggested: for heavy spalling a low impedance isolating layer between the tunnel liner and surrounding rock is recommended. For light rockfall, a simplified static FEM analysis procedure is presented.